The Relationship of Academic Stress, Self-Control, Social Exclusion with Smartphone Addiction in Junior High School Students - Triwahyuni Wardhany; Suroso Suroso; Muhammad Farid (STIKes Hang Tuah Pekanbaru, 2024)
The phenomenon of smartphone addiction in junior high school students needs serious attention to identify the factors that influence it. This study aims to analyze the relationship between academic stress, self-control, and social isolation and smartphone addiction in junior high school students. This research used a quantitative approach with 216 class VII and VIII subjects at SMP Negeri 2 Palangka Raya obtained using quota sampling. Data was obtained using the Smartphone Addiction Scale, Educational Stress Scale for Adolescents (ESSA), Brief Self-Control Scale (SCS), and General Belongingness Scale (GBS), which was then analyzed using Spearman's rho correlation analysis. The results of the research show that there is a positive relationship between academic stress and smartphone addiction in junior high school students. There is no relationship between self-control and smartphone addiction in junior high school students. There is a positive relationship between social isolation and smartphone addiction in junior high school students. Levels of smartphone addiction and academic stress tend to be high, while levels of self-control tend to be low to medium, and levels of social isolation tend to be moderate to low. The research suggests that it is essential to pay attention to academic stress and social isolation in order to prevent or overcome smartphone addiction in junior high school students.